Cell‐Penetrating Mitochondrion‐Targeting Ligands for the Universal Delivery of Small Molecules, Proteins and Nanomaterials. Issue 47 (6th July 2021) - Xiao, Qicai; Du, Wei; Dong, Xiao; Du, Shubo; Ong, Sing Yee; Tang, Guanghui; Zhang, Changyu; Yang, Fen; Li, Lin; Gao, Liqian; Yao, Shao Q.
Abstract: Mitochondria are key organelles that perform vital cellular functions such as those related to cell survival and death. The targeted delivery of different types of cargos to mitochondria is a well‐established strategy to study mitochondrial biology and diseases. Of the various existing mitochondrion‐transporting vehicles, most suffer from poor cytosolic entry, low delivery efficiency, limited cargo types, and cumbersome preparation protocols, and none was known to be universally applicable for mitochondrial delivery of different types of cargos (small molecules, proteins, and nanomaterials). Herein, two new cell‐penetrating, mitochondrion‐targeting ligands (named Mito Ligand ) that are capable of effectively "tagging" small‐molecule drugs, native proteins and nanomaterials are disclosed, as well as their corresponding chemoselective conjugation chemistry. Upon successful cellular delivery and rapid endosome escape, the released native cargos were found to be predominantly localized inside mitochondria. Finally, by successfully delivering doxorubicin, a well‐known anticancer drug, to the mitochondria of HeLa cells, we showed that the released drug possessed potent cell cytotoxicity, disrupted the mitochondrial membrane potential and finally led to apoptosis. Our strategy thus paves the way for future mitochondrion‐targeted therapy with a variety of biologically active agents. Abstract : Paving the way for future targeted therapy with a variety of biological agents. Cell‐penetrating mitochondrion‐targeting ligands are capable of universal mitochondrial delivery of small molecules, proteins and nanomaterials. Upon successful cellular delivery and rapid endosome escape, the released native cargos were found to be predominantly localized inside mitochondria. The successful delivery of doxorubicin (a well‐known anticancer drug) showed that the released drug possessed potent cell cytotoxicity, disrupted mitochondrial membrane potential and finally led to apoptosis.